FILOSOFI PENDIDIKAN DALAM PERMAINAN TRADISIONAL CUBLAK-CUBLAK SUWENG : MEMBANGUN KARAKTER DAN KEBERSAMAAN DALAM KONTEKS BUDAYA LOKAL - Sri Widayati, Ninuk; Setyawati, Lis; Darmuki, Agus; Kanzunnudin, Mohammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the effectiveness of elementary school learning based on local cultural wisdom through the use of the traditional song "Cublak-Cublak Suweng." It is expected that this research will contribute to the field of elementary education as well as the preservation of local culture, while also offering an innovative and contextual learning model.The song "Cublak-Cublak Suweng" was chosen as a learning medium because it contains important moral values that are easily understood by children. This research seeks to investigate the effectiveness of culture-based learning through the use of "Cublak-Cublak Suweng" among elementary school students.A qualitative research method was used, with data collected through observation, interviews, and relevant literature analysis. The results indicate that the song "Cublak-Cublak Suweng" is effective in instilling values such as cooperation, honesty, and togetherness in children. It also enhances student engagement and interest in learning activities.In addition, the song helps children to understand and appreciate their local culture, which is essential for the development of their cultural identity. Regularly singing this song in educational and family settings also strengthens children's social and emotional connections with their culture.This study concludes that the use of "Cublak-Cublak Suweng" as a medium for culture-based learning is an effective strategy to support the character and cultural development of young learners. Integrating this song into the elementary school curriculum can significantly contribute to the formation of character, moral values, and cultural understanding in children.